Reported outcome factors for pulmonary resection in metastatic colorectal cancer - Pfannschmidt, Joachim; Hoffmann, Hans; Dienemann, Hendrik (Journal of thoracic oncology, 2010)
Pulmonary resection of metastatic colorectal cancer is widely practiced in surgical oncology. However, only a highly selected subset of patients is eligible for resection, and the average recurrence rate is still high. We reviewed the recent literature on pulmonary metastasectomy for colorectal cancer and tried to address the issue of patient selection based on prognostic parameters associated with long-term survival. No randomized phase III trials are available, and data for this review were retrieved only from retrospective studies. We excluded papers reporting on patients earlier than 1990. In summary, there is a substantial body of evidence demonstrating that resection of pulmonary metastases can be performed safely and with a low mortality rate. For a subset of highly selected patients, the overall results of a 5-year actuarial survival rate after complete resection ranged between 40 and 68%. These outcomes exceed those normally associated with metastatic colorectal cancer. It is this perception that has encouraged surgeons and caused the practice to grow.
Elektronische Reproduktion der Druckausgabe
Gesehen am 02.05.2023